Standardization of Vegetative Propagation Techniques for Rooting of Populus alba Linn. Cuttings - Ramesh, K. R.; Khurana, D. K. (Indian Forester, 2007)
Populus alba cuttings were collected from Raksham (Kinnaur) of Himachal Pradesh during 1999-2000 to standardize the rooting hormones for rooting of P. alba cuttings. These were raised in the nursery of Dr. Y.S. Parmar University of Horticulture and Forestry Solan. It was concluded from the investigation that P. alba can be mass multiplied through shoot cuttings with the aid of 125 ppm IBA treatment. This concentration resulted in significant higher rooting per cent, root fresh weight, root dry weight, shoot fresh weight, shoot dry weight, internodal length and height. The simple correlation was calculated for all the auxin treatments/concentrations with respect to height, internodal length, root fresh weight, root dry weight, shoot fresh weight, shoot dry weight and rooting percentage. The observations for all those traits clearly indicated highly significant correlation's between all the traits at one per cent level of significance. Further all these traits i.e. Growth as well as biomass traits found to be positively correlated with each other. These correlation's may be exploited in a Tree improvement programme.